2017
DOI: 10.1016/j.psyneuen.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in associations between white matter microstructure and gonadal hormones in children and adolescents with prenatal alcohol exposure

Abstract: Despite accumulating evidence from animal models demonstrating that prenatal alcohol exposure (PAE) results in life-long neuroendocrine dysregulation, very little is known on this topic among humans with fetal alcohol spectrum disorders (FASD). We expected that alterations in gonadal hormones might interfere with the typical development of white matter (WM) myelination, and in a sex-dependent manner, in human adolescents with FASD. In order to investigate this hypothesis, we used diffusion tensor imaging (DTI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
(74 reference statements)
3
26
0
Order By: Relevance
“…The results of Treit et al might, therefore, stem from the effect of PAE on testosterone neurophysiological functioning. This hypothesis is well addressed in another fresh DTI study by Uban et al on adolescents using TBSS method(Uban et al, 2017). They surprisingly showed lower FA in white matter tracts in girls with PAE compared with healthy controls, while boys with PAE had higher FA relative to control boys; with no association between age and FA only in PAE boys.…”
mentioning
confidence: 86%
“…The results of Treit et al might, therefore, stem from the effect of PAE on testosterone neurophysiological functioning. This hypothesis is well addressed in another fresh DTI study by Uban et al on adolescents using TBSS method(Uban et al, 2017). They surprisingly showed lower FA in white matter tracts in girls with PAE compared with healthy controls, while boys with PAE had higher FA relative to control boys; with no association between age and FA only in PAE boys.…”
mentioning
confidence: 86%
“…Likewise, May and colleagues [ 23 ] recently reported that maternal drinking increases the males’ risk of mortality prior to birth but causes more growth impairments in females compared to their surviving male counterparts. The sex-specific effects of gestational alcohol exposure are also evidenced in the children’s dysregulated activation of the hypothalamic-pituitary-gonadal and hypothalamic-pituitary-adrenal axes as well as altered production of reproductive hormones and inflammatory markers [ 24 – 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that the abuse of alcohol impairs glial and astrocytic function [16]. Of important note, prenatal alcohol exposure alters the development of several brain regions, leading to structural and functional modifications in areas such as the cerebellum, cortex, and hippocampus [17], as well as white matter [18,19]. Alcohol-associated brain neuropathology can lead to behavior changes and impairments in learning, attention, executive functioning, and emotional regulation, which can seriously impact daily activities [20,21,22].…”
Section: Introductionmentioning
confidence: 99%